Information Revolution in Indian Agriculture - Bankey Bihari,; A.S. Mishra, (Journal of Agricultural Extension Management, 2025)
Indian agriculture contributes 32% to the G.D.P. and after 53 years of independence about 64% of Indian population still depend on agriculture. About 8 years are over when economic reforms were started in the country. Accordingly each and every sector has changed their strategies in view of global competition but for information dissemination at farmers level still age old concept of grassroot level worker and adopted villages & localities is continuing where after introduction of technology, years together you have to wait for its percolation to the remaining farm population. Even in adopted villages people take interest only till the project/programme is there, after project is over they again come to the point from where they had started, and despite providing free of cost extension services, so far, only 25-30% technologies have reached to the farmer’s field